Connecting the Drops : A Citizens' Guide to Protecting Water Resources - Schneller-McDonald, Karen (Book collections on Project MUSE., 2015)
The need for improved water resource protection, beginning with grassroots action, is urgent. The water we use depends on networks of wetlands, streams, and watersheds. Land-use activities, however, are changing these natural systems. Often these changes result in ecological damage, flooding, water pollution, and reduced water supply. We need a healthy environment that sustains our personal and community health; we also need vibrant and sustainable economic development that does not destroy the benefits we derive from nature. Our ability to accomplish both depends on how well we can "connect the drops."In this book, Karen Schneller-McDonald presents the basics of water resource protection: ecology and watershed science; techniques for evaluating environmental impacts; obstacles to protection and how to overcome them; and tips for protection strategies that maximize chances for success. Schneller-McDonald makes clear the important connections among natural cycles, watersheds, and ecosystems; the benefits they provide; and how specific development activities affect water quality and supply.The methods described in Connecting the Drops have broad application in diverse geographic locations. The environmental details may differ, but the methods are the same. For water resource managers and concerned citizens alike, Connecting the Drops helps readers interpret scientific information and contextualize news media reports and industry ads--ultimately offering "how to" guidance for developing resource protection strategies. Visit the website for this book at http://thewetnet.net.